Alterações das fibras musculares estriadas esqueléticas desnervadas e reinervadas em diferentes períodos - Morgueti, Marcelo (2005)
The objective of this work was to carry out an experimental study on the desnervation and the reinervation of the rat muscle soleus and also observe under morphologic and morphometric criteria, in which period after reinervation you can get a better standard of the related muscle. In order for that, twenty seven animals were used, aleatory divided in three groups of nine. In the group G1 (group zero day), it was carried out an incision between the tuber ischiatic and the trochanter bigger, where the sciatic nerve was dissected and sectioned in the height part of mid-thigh and immediately submitted to the technique of repair through the neurorhaphy terminus terminal. In the group G2 (group 10 days), the same procedure was carried out, but after the nervous section it was placed in the stump proximalis a polyethylene pipe of the blind fundus, fixed through wire 6-0. After ten days, the animals were again anesthetized to be submitted the reinervation through the described technique in group 1. In the group G3 (group 30 days), the same procedure was carried out, only differentiating the time and the wait of 30 days, to proceed the repair technique. The suture of the skin was made with the nylon wire 5-0. The animals had been sacrificed with superdosage of anesthetic, always after 10 days of repair to all groups. The removed muscle was first placed for some minutes in formaldehyde at 10% , to give form to the structure and after it was conditioned in appropriate container with formaldehyde 10% for twenty and four hours. After this period, the muscles were washed in running water for twenty and four hours and placed again in the same containers with alcohol 70%, until being taken to laboratorial procedures of routine. The gotten results had shown the success of the neurorrhaphy terminus terminalis in the recovery of the peripheral nervous without tissue loss, where in all groups the muscle fiber presented reinervation and the neuromuscular spindles, had kept with its normal intrafusal fiber numbers, understanding of 5 to 6 fiber in each one spindle.